Optimising the expansion of the National Bowel Cancer Screening Program - Cenin, Dayna R (Med J Aust, 2014)
OBJECTIVE(S): To estimate the impact of various expansion scenarios of the National Bowel Cancer Screening program (NBSCP) on the number of bowel cancer deaths prevented. Impact of the expansion scenarios on colonoscopy demand was also investigated. DESIGN: MISCAN-Colon, a well-established, validated computer simulation model for bowel cancer screening, was adjusted to reflect the Australian situation. In July 2013, we simulated the effects of screening over a 50 year period, starting in 2006. The model parameters included participation rates for screening and follow up, cancerous and pre-cancerous lesion identification rates, bowel cancer incidence, mortality and the outcomes of the NBCSP. Five implementation scenarios, based on biennial screening using an immunochemical faecal occult blood test, were developed and modelled. A sensitivity analysis that increased screening participation to 60% was also conducted. SETTING/ PARTICIPANTS: Australian residents aged 50 to 74 years MAIN OUTCOME MEASURES: Impact and comparison of five implementation scenarios on the number of bowel cancer deaths prevented and demand for colonoscopy. RESULTS: In its current state, MISCAN-Colon calculated that the NBCSP should prevent 35,169 bowel cancer deaths in the coming 40 years. Accelerating the expansion of the program to achieve biennial screening by 2020, more than 70,000 deaths would be prevented. If complete implementation of biennial screening resulted in a corresponding increase in participation to 60%, the number of deaths prevented increased across all scenarios. CONCLUSION(S): The findings strongly support the need for rapid implementation of the National Bowel Cancer Screening Program. Compared to the current situation, achieving biennial screening by 2020 could result in 100% more bowel cancer deaths being prevented (approximately 35,000) in the coming 40 years.